PENGUATAN NILAI MODERASI BERAGAMA MELALUI AJARAN AGAMA HINDU - Yunitha Asri Diantary Ni Made (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
Indonesia is a nation consisting of people with a diversity of cultures, religions, races, languages, ethnicities, traditions and others. The people are close to religious life and every religious activity is protected by the constitution. As the first precept in Pancasila which explains